2009
DOI: 10.1098/rspb.2009.1755
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent transmission of rotavirus in Great Britain and The Netherlands

Abstract: In Europe, rotavirus gastroenteritis peaks in late winter or early spring suggesting a role for weather factors in transmission of the virus. In this study, multivariate regression models adapted for time-series data were used to investigate effects of temperature, humidity and rainfall on reported rotavirus infections and the infection-rate parameter, a derived measure of infection transmission that takes into account population immunity, in England, Wales, Scotland and The Netherlands. Delayed effects of wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
62
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 42 publications
12
62
2
1
Order By: Relevance
“…The differences in the incidence rates could be primarily explained by the differences in target population, age groups that were investigated in each study, place and duration of each study, seasonal variation and size of sample of each study. In addition, it could be due to the influence of environmental conditions, hygiene practice, and level of sanitation as documented in studies by Atchison et al (2010), Levy et al (2009), Chandranet al (2006 and Ansari et al (1991) The findings of this study further revealed that the rate of rotavirus infections decreases with increase in the ages of the children (though not consistent) as most of the lowest number of positive cases, or even negative samples were found among the older age groups. For example, the highest number of positive cases of 9/21 (42.9%) was found among children aged 7 -12 months and the lowest rate of 0.5% was seen in two children, one aged 31 -36 months and the other 13 -48 months.…”
Section: Discussionsupporting
confidence: 55%
“…The differences in the incidence rates could be primarily explained by the differences in target population, age groups that were investigated in each study, place and duration of each study, seasonal variation and size of sample of each study. In addition, it could be due to the influence of environmental conditions, hygiene practice, and level of sanitation as documented in studies by Atchison et al (2010), Levy et al (2009), Chandranet al (2006 and Ansari et al (1991) The findings of this study further revealed that the rate of rotavirus infections decreases with increase in the ages of the children (though not consistent) as most of the lowest number of positive cases, or even negative samples were found among the older age groups. For example, the highest number of positive cases of 9/21 (42.9%) was found among children aged 7 -12 months and the lowest rate of 0.5% was seen in two children, one aged 31 -36 months and the other 13 -48 months.…”
Section: Discussionsupporting
confidence: 55%
“…It was more common in the summer months, contrasting with the pattern observed in people and cattle in the United Kingdom, where rotavirus is considered a cold weather disease (32,47,48). In worldwide surveillance studies, country income level is a more reliable predictor of infection than is latitude or geographical location.…”
Section: Discussionmentioning
confidence: 72%
“…38,39 The 5-week period is also several times longer than the incubation periods of rotavirus, E. coli, and often, Giardia, allowing enough time for secondary transmission events to noticeably affect diarrhea prevalence. 15,40 This study was carried out over a 6-month period (from the beginning to the end of a rainy season). It is possible that the overall decline in diarrhea from the beginning to the end of the rainy season was the result of a reporting bias.…”
Section: Discussionmentioning
confidence: 99%